Nilai Pendidikan dalam Drama Tragedi Neng-Nong Karya M. Udaya Syamsuddin - Aziz, Ikhsan Abdul (Universitas Suryakancana, 2024)
Every literary work, including drama, generally expresses noble values that are beneficial for readers and audiences. Values in literary works are sometimes referred to as mandates. Thus, in the drama script there are educational values that need to be studied. The method used in the research is descriptive qualitative. Research findings show that the drama